2021
DOI: 10.3233/nre-210139
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study verifying the effectiveness of high-frequency repetitive transcranial magnetic stimulation in combination with intensive speech-language-hearing therapy in patients with chronic aphasia

Abstract: BACKGROUND: A lot of research on the effectiveness of repetitive transcranial magnetic stimulation (rTMS) in patients with aphasia in the chronic stage deals with low-frequency stimulation, and reports on high-frequency stimulation (HF-rTMS) are scarce. OBJECTIVE: The purpose of this study was to evaluate retrospectively the effectiveness of high-frequency rTMS in combination with intensive speech-language-hearing therapy (ST) following the identification of the stimulation site using functional magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…We recently reported that aphasia in patients who are independent in their daily lives can be improved through repetitive high-frequency transcranial magnetic stimulation and speech and hearing training targeted at areas of language activation identified during a recitation task using functional magnetic resonance imaging [38]. It is noteworthy that patients with aphasia and higher brain dysfunction benefit from responding aloud to tasks rather than simply contemplating them internally.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that aphasia in patients who are independent in their daily lives can be improved through repetitive high-frequency transcranial magnetic stimulation and speech and hearing training targeted at areas of language activation identified during a recitation task using functional magnetic resonance imaging [38]. It is noteworthy that patients with aphasia and higher brain dysfunction benefit from responding aloud to tasks rather than simply contemplating them internally.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled double-anonymized trial found significant improvements in language function in 12 patients with subacute-phase aphasia who received 14 days of 1 Hz rTMS and speech training in the right hemisphere inferior frontal gyrus, with repetition and comprehension achieving moderate effects and naming achieving smaller effects [ 58 ]. Khedr et al [ 59 ] recruited 15 patients with subacute phase aphasia and applied 1 Hz rTMS to the right subfrontal gyrus of the patients and 20 Hz rTMS to the left subfrontal gyrus and found a significant improvement in speech scores after 10 days and 2 months of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, high-frequency rTMS upregulates neuronal activity, low-frequency rTMS downregulates it [ 17 ]. At present, it is unknown whether the right or left cerebral hemisphere is significant in terms of the recovery course of language functions in aphasia in the chronic stage [ 6 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with repetitive transcranial magnetic stimulation (rTMS) for post-stroke aphasia facilitates recovery of language function by regulating cerebral cortex excitability. The department of rehabilitation medicine of The Jikei University School of Medicine started performing rTMS therapy for patients with aphasia following stroke in 2008, and reported the efficacy of the therapy [ 3 10 ]. The latest international rTMS guidelines 2020 recommend rTMS therapy in post-stroke aphasia as level B of evidence (probable efficacy) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%